Eye Gaze and Dominance, Cues for Online Communication with Strangers - Beril Durmuş; Yonca Aslanbay; Murat Çinko; Aydin Erden (Türkiye İletişim Araştırmaları Dergisi)
Many digital communication platforms of the new economy are built up on mechanisms to initially communicate and/or develop an acquaintance with “strangers” over displayed profile pictures. This study aims to reveal the impact of the direction of eye gaze and perceived dominance from those pictures during the process of pairing online with a stranger, for spending time in a closed environment. Preference between pairs of 66 participants through their profile pictures having a direct or averted gaze and some manipulated by facial width height ratio (fWHR) aiming to increase perceived dominance, were measured by the eye- tracking device. The findings show that when observing the profile pictures of strangers (i) gaze attracts attention to the face of gazing person, (ii) in case of perceived dominance, the gaze of a stranger induces gaze avoidance for participants. The study further predicted when the user is to prefer between pairs of people that one is perceived to be dominant, the probability of choosing the perceived non-dominant is higher. The participants’ preference of the former holdout sample was predicted consecutively by hit ratios of 81.5, 91.4 and 94.9 for three different cases. Analysis of the data revealed no systematic differences between males and females.